الفهرس العام لمخطوطات المكتبة البارونية - الباروني, سعيد بن يوسف (2019)
Keywords: Bibliothèques – Djerba; Catalogue – Djerba; Manuscrits – Djerba

Le catalogue de la bibliothèque al-Bāsī : circulation et thésaurisation du savoir à Djerba - Madani, Sarra (Ecole Pratique des Hautes Etudes, 2019)
Don de l'auteure
Keywords: Basi; mosquée al- (Oualegh; Djerba); Bibliothèques – Djerba; Manuscrits – Djerba

Ibadi Manuscripts in non-Ibadi Libraries | المخطوطات الإباضية بالمكتبات غير الإباضية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
Ibadi libraries, almost without exception, house non-Ibadi books. Sometimes, Ibadi-owned libraries held hundreds of titles by non-Ibadi authors and those titles far outnumbered the Ibadi ones. When…
Keywords: Manuscrits – Djerba

EAP1216 “The Djerba Libraries Project:” A New Manuscript Digitization Project in Djerba, Tunisia | مكتبات جربة: مشروع جديد لرقمنة المكتبات بجربة (تونس) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
I am delighted to announce the launch of “EAP1216 The Djerba Libraries Project,” a two-year effort to digitize several libraries on the island of Djerba, Tunisia. Funded by Arcadia (a c…
Keywords: Manuscrits – Conservation; Manuscrits – Djerba

مخطوطات عمانية في خزانة سالم بن يعقوب الجربي - العيسري, محمد بن عامر (الذاكرة, 2019)
Keywords: Bibliothèques – Djerba; Manuscrits – Djerba

Curating Ibāḍī Archives: Notes on the Social Life and Archival Logic of the Bin Yaʿqūb Family Library in Jerba,Tunisia - Love Jr, Paul M. (Local and global Ibadi identities, 2019)
Keywords: Manuscrits – Djerba